2010
DOI: 10.1124/jpet.110.171975
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Enhances ATP-Induced Inflammatory Responses in Endothelial Cells

Abstract: The purinergic nucleotide ATP is released from stressed cells and is implicated in vascular inflammation. Glucocorticoids are essential to stress responses and are used therapeutically, yet little information is available that describes the effects of glucocorticoids on ATP-induced inflammation. In a human microvascular endothelial cell line, extracellular ATP-induced interleukin (IL)-6 secretion in a dose-and time-dependent manner. When cells were pretreated with dexamethasone, a prototypic glucocorticoid, AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…Upon stimulation, the TLR2 signaling leads to the activation of proinflammatory transcription factors and results in the expression of inflammatory cytokines [65,66]. Second, GCs can upregulate the expression of pyrin domain-containing 3 [62,67] and purinergic 2Y2 nucleotide receptor [68], which can sensitize innate immune cells to extracellular adenosine triphosphate and ultimately induce the synthesis of proinflammatory cytokines [65,66]. Third, NMDA signaling may participate in the process of GC-priming microglia [69].…”
Section: Discussionmentioning
confidence: 98%
“…Upon stimulation, the TLR2 signaling leads to the activation of proinflammatory transcription factors and results in the expression of inflammatory cytokines [65,66]. Second, GCs can upregulate the expression of pyrin domain-containing 3 [62,67] and purinergic 2Y2 nucleotide receptor [68], which can sensitize innate immune cells to extracellular adenosine triphosphate and ultimately induce the synthesis of proinflammatory cytokines [65,66]. Third, NMDA signaling may participate in the process of GC-priming microglia [69].…”
Section: Discussionmentioning
confidence: 98%
“…4C) has considerable implications for processes that result in micromolar levels of extracellular ATP in vivo, such as inflammation (53), damaged and dying tissue (54), or chemotherapy (55). In addition to changes in NLRP3, induction of P2Y 2 by glucocorticoids could be contributing to this sensitization and providing another pathway for ATP and GR to crosstalk (47).…”
Section: Discussionmentioning
confidence: 99%
“…Acute stress has been shown to prime the immune system and enhance the release of TNF-␣, IL-1␤, and IL-6 (45,46). Additionally, it recently has been shown that glucocorticoids enhance the release of IL-6 from endothelial cells in response to ATP (47). Therefore, supernatants from LPS-primed THP-1 and THP-M⌽ were assayed for the secreted forms of the following pro-and anti-inflammatory cytokines by flow cytometry: IL-8, IL-1␤, IL-6, IL-10, TNF-␣, and IL-12 p70.…”
Section: Glucocorticoids Specifically Regulate Nlrp3 But Not Othermentioning
confidence: 99%
“…In a human microvascular endothelial cell line, dexamethasone enhanced ATP-induced interleukin 6 (IL-6) secretion through PLC and p38 MAPK. In addition, dexamethasone induced P2Y 2 receptor mRNA expression, and when the P2Y 2 receptor was silenced by its small interfering RNA, ATPinduced IL-6 production decreased [126]. Dexamethasone also enhanced the ATP-induced [Ca 2+ ]i increase and nitric oxide (NO) production in type I spiral ganglion neurons of the guinea pig cochlea.…”
Section: P2 Receptors and Steroid Hormone Receptorsmentioning
confidence: 90%